About time and language - Agnė Navickaitė-Klišauskienė; Eglė Žilinskaitė-Šinkūnienė (Vilnius University Open Series, 2022)
The paper presents the former etymologies of the heterosemantic cognates Lith. valanda and La. valoda with a special focus on their relation and origin from the motion verbs described by Edīte Hauzenberga-Šturma. On the basis of the old writings and corpora we provide additional arguments to show that both time and language can be conceptualized as (cyclically) moving phenomena.